Social Responsibility and Ethics as Effective Advertising Strategies - Gutiérrez Gutiérrez, María Margarita (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective is to analyze from ethics, morality, codes of ethics, Environmental Management Systems, Corporate Social Responsibility, self-regulation, advertising regulation and co-regulation, how these parameters can impact companies and their brands, in cases were through advertising and marketing, they communicate their actions and results to society. Methodologically, hermeneutics and qualitative and quantitative analysis were used, using a Colombian oil company as a case study. Concluding that in this case and in many others, these advertising strategies are business effective.